Understanding the Promotion of Self-Regulated Learning in Upper Secondary Schools: How can Teaching Quality Criteria contribute? - Mejeh, Mathias; Stampfli, Barbara; Hascher, Tina (Frontline Learning Research, 2024)
Self-regulated learning (SRL) has gained increasing attention in educational science over the past four decades. Especially within the context of the lifelong learning debate, regulatory strategies play a crucial role, as they are essential not only within schools and classrooms but also in lifelong learning contexts. Concurrently, the discussion on teaching quality holds an equally central position in educational science. However, these two lines of discourse have, so far, been treated largely independently of each other and lack an alignment. In our exploratory study, we applied the three basic dimensions of teaching quality to assess an SRL-promoting learning environment from the perspective of students. We conducted seven focus groups involving a total of N = 49 secondary school students, and the data was analyzed using qualitative content analysis. Our analyses demonstrate that these basic dimensions can contribute to analyze the quality of an SRL environment. However, further adaptation is required as the three dimensions seem still to be interwoven with a more traditional conceptualization of teaching.